Making the Most of Our Land: Managing Soil Functions from Local to Continental Scale - Schulte, Rogier P. O.; Bampa, Francesca; Bardy, Marion; Coyle, Cait; Creamer, Rachel E.; Fealy, Reamonn; Gardi, Ciro; Ghaley, Bhim Bahadur; Jordan, Phil; Laudon, Hjalmar; O'Donoghue, Cathal; Ó'hUallacháin, Daire; et al. (Frontiers in Environmental Science, 2015)
The challenges of achieving both food security and environmental sustainability have resulted in a confluence of demands on land within the European Union (EU): we expect our land to provide food, fiber and fuel, to purify water, to sequester carbon, and provide a home to biodiversity as well as external nutrients in the form of waste from humans and intensive livestock enterprises. All soils can perform all of these five functions, but some soils are better at supplying selective functions. Functional Land Management is a framework for policy-making aimed at meeting these demands by incentivizing land use and soil management practices that selectively augment specific soil functions, where required. Here, we explore how the demands for contrasting soil functions, as framed by EU policies, may apply to very different spatial scales, from local to continental scales. At the same time, using Ireland as a national case study, we show that the supply of each soil function is largely determined by local soil and land use conditions, with large variations at both local and regional scales. These discrepancies between the scales at which the demands and supply of soil functions are manifested, have implications for soil and land management: while some soil functions must be managed at local (e.g., farm or field) scale, others may be offset between regions with a view to solely meeting national or continental demands. In order to facilitate the optimization of the delivery of soil functions at national level, to meet the demands that are framed at continental scale, we identify and categorize 14 policy and market instruments that are available in the EU. The results from this inventory imply that there may be no need for the introduction of new specific instruments to aid the governance of Functional Land Management. We conclude that there may be more merit in adapting existing governance instruments by facilitating differentiation between soils and landscapes.